Cover crop-based reduced tillage management impacts organic squash yield, pest pressure, and management time - Bruce, Dylan; Silva, Erin M.; Dawson, Julie C. (Frontiers in Sustainable Food Systems, 2022)
Cover crop-based reduced tillage (CCBRT) systems can provide multiple benefits in cucurbit cropping systems, including potential to reduce spread of soil-borne pathogens, minimize erosion, and decrease weed pressure. Despite benefits and farmer interest, adoption has been limited, in part due to inconsistent weed suppression and potential for reduced yields. Prior studies have suggested that N competition, allelopathy, and lower temperature may be factors in reducing vegetable yield in CCBRT systems. A strip tillage approach has been suggested as one strategy that could mitigate those issues, but cucurbit yields using these systems have shown mixed results in prior studies, some of which did not include other important considerations for growers such as the impact on weed and pest pressure. In 2018 and 2019, CCBRT strip till practices for organic acorn winter squash (Cucurbita pepo L.) production were assessed in Wisconsin on certified organic land. Combinations of different between-row (aisle) and in-row mulches were compared to attempt to identify reduced tillage combinations that effectively manage weeds while resulting in yields comparable to full tillage production, testing our hypothesis that no differences between production systems would be observed due to strip tillage and plastic mulch warming soil and minimizing competition while promoting cash crop growth. Aisle treatments included roller-crimped cereal rye (Secale cereale L.) mulch, straw mulch and cultivated bare ground, and in-row treatments included plastic mulch, ground straw mulch, and cultivated ground. Weed and pest counts, weed management time, and yields were compared between treatments. Plots managed with rye and straw in the aisles had significantly less weed pressure as compared to cultivated aisle treatments, although rye required more weed management time than ground straw mulch. In addition, rye resulted in lower marketable yield due to higher proportion unmarketable fruit in 2018, likely related to a 25 cm rain event 2 weeks prior to harvest. A significant row mulch × aisle mulch interaction was observed for marketable fruit m−1, showing that yield was not significantly affected by the type of in-row mulch in plots with crimped rye mulch in the aisle. Pressure from squash bugs (Anasa tristis) was also higher in treatments with organic or synthetic mulches (straw in aisles or rows, rye in aisles, and plastic in rows). Our results support previous evidence that crimped rye can be an effective mulching strategy to reduce weed pressure, with more efficient management than traditional straw mulch. However, crimped rye systems may have negative implications for yield and pest pressure regardless of the use of a strip-tillage approach, indicating that more research is needed to refine the production system.